Respons Kedelai Edamame terhadap Berbagai Jarak Tanam dan Dosis Pupuk Kotoran Ayam - Budiyati Ichwan; Ridwan M; Eliyanti Eliyanti; Irianto Irianto; Cici Pebria (Jurnal Media Pertanian, 2021)
Efforts to increase edamame production and productivity include regulating plant populations and increasing soil fertility. The aim of the study  was to examine the response of edamame soybeans to various spacings and doses of chicken manure. The study aimed to examine the response of edamame soybeans to various spacings and doses of chicken manure. The experiment used a Randomized Block Design (RBD) with two factors, namely plant spacing which included: 30cm x 10cm; 30cm x 20cm; 30cm x 30cm, and the dose of chicken manure fertilizer is: 5 tons ha-1; 10 tons ha-1, and 20 tons ha-1. Plant spacing and dose of chicken manure did not significantly affect, but each factor affected the number of branches, as well as the number and fresh weight of edamame pods. Edamame gave the best response at a spacing of 30cm x 20cm and a dose of chicken manure 15 tons ha-1. Edamame productivity from this study was only able to meet 48 – 50% of the productivity target for exports.